Non EFL Students' Perception in English Language Learning Strategies (LLS) in the Digital Era - Muliaty Ibrahim; Dewi Nidia Soepriadi; Sunarlia Limbong; Sujarwo Sujarwo; Luana Sasabone (STAI Hubbulwathan Duri, 2023)
This study was carried out in perception to the demand that in this 4.0 era, Indonesian students should be proficient in English. Hence, in Indonesia, English has been taught and learnt since elementary school level up to tertiary level of education. This study aims to examine non EFL students' English learning strategies in ESP learning; especially regarding the types of strategies used most often and the tendency of non EFL students to use these strategies. This study used a qualitative approach with a descriptive case study method involving 37 Medical Laboratory Technician students. They were selected by stratified random sampling. The instrument used is a questionnaire adapted from Oxford (1990). The results of study showed that non EFL students were not very aware of the use of language learning strategies in learning English as a foreign language because they rarely used them. However, non EFL students had priority affective strategy (24.3%), social strategy (22.3%), followed by compensation strategies (19.3%), cognitive (11.4%), metacognitive (14.3%), and memory strategies (8.4%). Based on the research results, it is expected that non EFL students can recognize and learn foreign language learning strategies comprehensively, which must be applied continuously to achieve success.